Watchmen - Moore, Alan, 1953- (DC Comics, 2019)
"Considered the greatest graphic novel in the history of the medium, the Hugo Award-winning story chronicles the fall from grace of a group of superheroes plagued by all-too-human failings. Along the way, the concept of the superhero is dissected as an unknown assassin stalks the erstwhile heroes."--Publisher.